Evaluating ICU nurses’ education, practice, and competence in palliative and end-of-life care in Saudi Arabia: A cross-sectional study - Afaf Alrimali; Nashi Alreshidi (Belitung Nursing Journal, 2024)
Background: In palliative and end-of-life (PEOL) care, especially within intensive care units (ICUs), nurses’ unique skills are critical, yet their expertise remains under-explored, particularly in Saudi Arabia Objective: This study aimed to evaluate the education, practice, and perceived competence of adult ICU nurses in Saudi Arabia regarding PEOL care and to pinpoint key factors that influence this aspect of healthcare delivery. Methods: A cross-sectional design was utilized in this study. Participants were recruited from five public hospitals and one specialized center in Hail, Saudi Arabia. Data were gathered in September 2023 using the PEOL Care Index, which measures various care dimensions on a Likert scale in Arabic and English. IBM SPSS Statistics 29.0 was used for statistical analysis, particularly to conduct ANOVA, t-test, and multiple regression. Results: 142 out of the targeted 171 ICU nurses completed the survey, yielding a response rate of 83.04%. Although 81% of the nurses had experience caring for dying patients, only 30.3% had received in-service PEOL care training. Those with this training demonstrated significantly higher scores in education, clinical practice, and perceived competence than their counterparts (p <0.05). Mean scores across these areas were 69.67, 71.01, and 71.61, respectively. In-service training positively correlated with these metrics (p <0.05). Multiple regressions also revealed that in-service training, job satisfaction, and communication authority are strong influencers, explaining 21.6% of the variation in clinical practice and 16.9% in perceived competence. Conclusion: The study highlighted the proficiency of ICU nurses in PEOL care, emphasizing that in-service training, job satisfaction, and the authority to communicate effectively with patients and their families significantly improved clinical practice and nurses’ competence in PEOL care. This underlines the critical need for healthcare institutions to acknowledge and address these key factors to optimize patient care outcomes.